The Role of The Principal Leadership in Developing Sustainable Students Character Education - Fathulmila Matiala, Tiara; Ayu Anggreni , Made; Sandra Lumingkewas , Cindy; Sofyanty , Devy; Bashori , Bashori (Mudir : Jurnal Manajemen Pendidikan, 2023)
The goal of this study is to describe the principal's initiatives to advance character education as well as his or her leadership role in its development. Descriptive analysis is a qualitative method that was employed in this investigation. Techniques like observation, interviews, and documentation were used in this study. According to the study's findings, the school principal can be viewed playing a leadership role in the development of character education through the planning, carrying out, and overseeing of character education development activities. The principle has included character values like self-assurance, reason, logic, and creativity into the programmers and activities he has created. Through oversight, monitoring, and assessment of the planning, execution, and outcomes of character education implementation, the school principal manages and directs the character education programmer. All parties involved in the school are involved in the character education implementation.